2021
DOI: 10.3389/fenvs.2021.800878
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Military Expenditure, Tourism, and Exports for Sustainable Economic Growth

Abstract: The current empirical study addresses the recent economics of Saudi Arabia such as the uncertainty of economic growth and dependence on oil export. For this purpose, labor, capital, oil price, terrorism, military expenditure, tourism, and exports are added to the analysis. ARDL long-run and short-run analyses are used, and the results of the study have revealed that labor is negatively related to economic growth, which suggests that efforts should be done to reduce dependence on international labor through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…For this purpose, labor, capital, oil prices, terrorism, military spending, tourism and exports are added to the analysis. Through short-term and long-term analysis, there is a systematic effect between economic freedom and GDP of the military, or vice versa (Aziz et al, 2021). Dudzevičiūtė & Šimelytė (2022) examines the relationship between the defense burden in NATO countries and economic indicators.…”
Section: Justificationmentioning
confidence: 99%
“…For this purpose, labor, capital, oil prices, terrorism, military spending, tourism and exports are added to the analysis. Through short-term and long-term analysis, there is a systematic effect between economic freedom and GDP of the military, or vice versa (Aziz et al, 2021). Dudzevičiūtė & Šimelytė (2022) examines the relationship between the defense burden in NATO countries and economic indicators.…”
Section: Justificationmentioning
confidence: 99%
“…Aziz et al (2021) analysed the impact of military expenditure, tourism, and exports on the Saudi Arabian economy using the ARDL framework. Findings revealed that terrorism and military expenditure does not significantly influence economic growth in Saudi Arabia but tourism does.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that while terrorism stifles growth in the selected countries, military expenditure plays a key role in moderating the debilitating effect of terrorism on growth in the countries. Aziz et al (2021) analysed the impact of military expenditure, tourism, and exports on the Saudi Arabian economy using the ARDL framework. Findings revealed that terrorism and military expenditure does not significantly influence economic growth in Saudi Arabia but tourism does.…”
Section: Role Of Military Expenditure In the Terrorism-tourism Nexusmentioning
confidence: 99%